Alash publicism and journalistic activity of Alikhan Bukeikhan - Tatiana Lebedeva, Alma Sailaukyzy, Kairat Sak, (Opción, 2019)
The article analyzes the journalistic activity of Alikhan Bukeikhan via source analysis of the literature on the subject. We consider the position of the authorities on the work of Alikhan. Methods of Alikhan’s political struggle, their influence on his professional journalistic activity are also considered in the article. As a result of his actions, Alikhan Bukeikhan became the founder of professional Kazakh journalism, he created the first nationwide newspaper, which was published in the Kazakh language – Qazaq. As a conclusion, Alikhan is one of the heroes of the national movement in Kazakhstan.